Strategy to Suppress Intention to Leave with Stress Impact Analysis, Workload and Conflict in The Workplace A Study of Educational Staff in Bogor City - Jumadi, Jumadi; Yusnita, Nancy; Sunaryo, Widodo (Riviera Publishing, 2025)
This research aims to analyze the impact of job stress, workload, and work conflict on the intention to leave (ITL) among education personnel in private elementary schools in Bogor City, Indonesia. Employing an explanatory sequential mixed-methods design, this study quantitatively tests Gibson et al.'s stress model on a sample of educational personnel, followed by qualitative exploration to enrich the understanding of the quantitative findings. The research results indicate that excessive workload and unresolved work conflict significantly contribute to increased levels of job stress among the education personnel. Furthermore, path analysis reveals that job stress plays a crucial mediating role between workload and work conflict with the intention to leave. In other words, workload and work conflict indirectly increase the desire to leave the job by increasing the experienced stress. The practical implications of these findings lead to the formulation of intervention strategies aimed at reducing intention to leave through the management of organizational stressors. Private elementary schools need to focus on alleviating unrealistic workloads, minimizing sources of internal conflict, and developing effective stress management programs to enhance the retention of their educational personnel. This study provides valuable insights for school management in creating a more conducive and sustainable work environment.